2022
DOI: 10.22146/jpki.72842
|View full text |Cite
|
Sign up to set email alerts
|

Readiness for Interprofessional Education: Perspective From Medical and Nursing Students

Abstract: Background: Interprofessional education (IPE) is argued as an educational strategy for promoting communication and collaboration amongst prospective healthcare professionals. The benefits of IPE have culminated in improved patient care leading to enhanced satisfaction for patients and healthcare practitioners. Therefore, further exploration is needed to assess the readiness for IPE through healthcare students’ perspectives, specifically medical and nursing students.This study aimed to assess medical and nursin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…The results indicated that female students had significantly greater IEPS scores than male students, z = -2.23, p = 0.026. This finding differs from other studies which have found that there was no difference between sex in terms of IEPS scores (29,30).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The results indicated that female students had significantly greater IEPS scores than male students, z = -2.23, p = 0.026. This finding differs from other studies which have found that there was no difference between sex in terms of IEPS scores (29,30).…”
Section: Resultscontrasting
confidence: 99%
“…Moreover, for this study, the total scores of modified IEPS and RIPLS are divided into three categories; good, intermediate, and bad, using the determination of the instrument category based on the interval formula (27). The categories for the modified IEPS instrument were eventually divided into three, namely good (52-72), moderate (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51), and bad (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). The RIPLS questionnaire categories were divided into three, namely good (58.7 -80), moderate (37.4 -58.6) and bad (16 -37.3).…”
Section: Study Instrumentmentioning
confidence: 99%
“…A study conducted at UPH (Universitas Pelita Harapan) Tangerang, Indonesia, examined the readiness of pre-clinical students and faculty members at the Faculty of Medicine (FoM) and Faculty of Nursing (FoN) for IPE [ 11 ]. Students were more prepared for interprofessional learning, including teamwork collaboration and an understanding of their professional identities, but less prepared for understanding their roles and responsibilities in IPE.…”
Section: Introductionmentioning
confidence: 99%